Electrochemical kinetic study of surface layer growth on natural pyrite in acid medium - Giannetti, B. F.; Almeida, CMVB; Bonilla, S. H. (Elsevier B.V., 2006)
This paper presents electrochemical experiments on natural pyrite that combine potentiostatic and voltammetric techniques. X-ray microanalysis is used as an auxiliary technique. The layer growth on pyrite surface is conducted in a wide range of pH and potential range: 3.4 <= pH <= 5.9 with E = 0.80 V (versus SHE), and 0.80 V <= E <= 1.00 V with pH 4.5 (versus SHE) in acetic acid-acetate buffer. This work is unique for two reasons: (1) phenomenological model about layer growth is applied and mathematical-physic consistence is verified and (2) Meyer's hypotheses of chemical mechanism are used to explain kinetic parameters of the phenomenological model. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: kinetic model; pyrite; surface